Tetramethylpyrazine Enhances Vascularization and Prevents Osteonecrosis in Steroid-Treated Rats - Jiang, Yini (Biomed Res Int, 2015)
Steroid-induced osteonecrosis of the femoral head (steroid-induced ONFH) is an avascular necrosis disease of bone. Tetramethylpyrazine (TMP), with significant vascular protective properties, has been widely used for the treatments of ischemic neural disorders and cardiovascular diseases. However, its role in the treatment of steroid-induced ONFH has not been evaluated. In this study, our results showed that TMP significantly decreased the ratio of empty lacuna, adipose tissue area, and adipocyte perimeter in steroid-induced ONFH rats histopathologically. TMP also reduced the levels of serum lipid dramatically by haematological examination. According to the micro-CT quantification, TMP could improve the microstructure of the trabecular bone and increases bone mineral density in steroid-induced ONFH rats. Moreover, TMP significantly increased the vessel volume, vessel surface, percentage of vessel volume, and vessel thickness of the femoral heads by micro-CT. Interestingly, the downregulation of VEGF and FLK1 proteins in the sera and necrotic femoral heads could be reversed by TMP treatment, and this was true for their mRNA expressions in femoral heads. In conclusion, these findings suggest for the first time that TMP may prevent steroid-induced ONFH and also enhance femoral head vascularization by inhibiting the effect of steroid on VEGF/FLK1 signal pathway.